PENYULUHAN TENTANG PENGGUNAAN HELM SNI PADA MAHASISWA KESEHATAN MASYARAKAT UNIVERSITAS PAHLAWAN TUANKU TAMBUSAI - Rizki Rahmawati Lestari; Etri Gustiana (Universitas Pahlawan Tuanku Tambusai, 2022)
Helmets are a form of body protection worn on the head and are usually made of metal or other hard materials such as kevlar, resin fibers, or plastic. Helmets are usually used as head protection for various combat (military) activities, or civilian activities such as sports, mining, or driving. Helmets can provide additional protection of part of the head (depending on the structure) from falling or high-velocity objects. Motorcycle drivers on the highway have behaviors that tend to be more dangerous than other vehicle drivers. This can be seen that there are still many motorcycle drivers who do not use safety attributes, especially helmets to reduce the risk in the event of an accident. In addition to helmets, the attributes of driving equipment must also be considered to make driving safer and more comfortable. Such as using shoes, using a jacket and trousers and if necessary using a mask and gloves, which function to grip the motorcycle handlebars to make it more comfortable and steady (Wibowo, 2011). Severe head injuries account for the largest share of accidents experienced by motorcyclists. Types of head damage in the form of cracks in the cranium, injuries to the forehead or face, the back or sides of the head. This is where the SNI helmet performs its function in order to reduce the level of injury to the head. People's behavior to wear standard helmets is still low, many motorcycle riders still use helmets as they are (not meeting the standards), as well as many circulating non-standard helmets. The price of a standard helmet that is widely sold in the market is relatively expensive, so it is very burdensome for those who have mediocre income. Knowledge, and trust in people who think standard helmets are no different from normal helmets. Standard helmets are considered inconvenient and can reduce vision, especially at night, hot until the wearer sweats. Some of these helmet users just cover their heads so they are not ticketed by police officers. Keywords: Helm SNI, Counseling